Prospective impact of tobacco eradication and overweight and obesity eradication on future morbidity and health-adjusted life expectancy: simulation study. Issue 4 (20th January 2020) - Blakely, Tony; Cleghorn, Cristine; Petrović-van der Deen, Frederieke; Cobiac, Linda J; Mizdrak, Anja; Mackenbach, Johan P; Woodward, Alistair; van Baal, Pieter; Wilson, Nick
Abstract : Background: Interventions that reduce morbidity, in addition to mortality, warrant prioritisation. It is important to understand the magnitude of potential morbidity and health gains from changing risk factor distributions. We quantified the impact of tobacco compared with overweight/obesity eradication on future morbidity and health-adjusted life expectancy (HALE) for the New Zealand population alive in 2011. Methods: Business-as-usual (BAU) future smoking rates were set based on past falling rates, but we assumed no future change in Body Mass Index (BMI) distribution, given historic trends. Population impact fractions and the percentage reduction in incidence rates for 16 tobacco-related and 14 overweight/obesity-related diseases (allowing for time lags) were calculated using the difference between BAU and eradication risk factor scenarios combined with tobacco and BMI incidence rate ratios. We used two multistate lifetable models to estimate HALE changes over the remaining lifespan and morbidity rate changes 30 years hence. Results: HALE gains always exceeded life expectancy (LE) gains for overweight/obesity eradication (ie, absolute compression of morbidity), but for eradication of tobacco, the pattern was mixed. For example, among 32-year-olds in 2011, overweight/obesity eradication increased HALE by 2.06 years and LE by 1.21 years, compared with 0.54 and 0.50 years for tobacco eradication. Morbidity rate reductions 30 years into the future were considerably greater for overweight/obesity eradication (eg, a 15.8% reduction for 72-year-olds in 2041, or the cohort that was aged 42 years in 2011) than for tobacco eradication (2.7%). The same rate of morbidity experienced at age 65 years under BAU was deferred by 5 years with overweight/obesity eradication. Conclusions: Preventive programmes that reduce overweight and obesity have strong potential to reduce or compress morbidity, improving the average health status of ageing populations. This paper simulated eradication of tobacco and overweight/obesity; actual interventions will have lesser health impacts, but the relativities of morbidity to mortality gains should be similar.